Food microblology analisys. Coagulase-positive Staphylococcus count method verification acording to ISO 16140. - Rubio Cumplido, María; Díaz Simón, Verónica (Biosaia: Revista de los másteres de Biotecnología Sanitaria y Biotecnología Ambiental, Industrial y Alimentaria, 2023)
Staphylococcus aureus and other coagulase-positive staphylococcus are bacteria with the capacity to produce staphylococcal enterotoxins, that can produce a lot of food poisonings manifested as nausea, vomits and diarroheas. The Spanish Association for Standardization (UNE in Spanish) has published some changes to the specifications that specify methods for coagulase-positive Staphylococcus count [1]. One of these rules, the UNE-EN ISO 6888-1:2021, is the one that has been followed in this Master's Thesis, together with the verification according to ISO 16140 [2]. UNE-EN ISO 6888-1:2021 details a horizontal method for counting coagulase-positive staphylococci by counting the colonies obtained on a solid medium (Baird-Parker) after an incubation period between 34 and 38 ºC. After this, the confirmation by coagulase takes place [1]. In this case, the test is carried out on 5 samples of 5 different foods: egg, meat, cheese, cake and cooked food. Colonies suspected of being coagulase-positive staphylococci are black or gray, shiny, and convex and surrounded by a translucent halo that may be partially opaque. After 24 h of incubation, a count of those typical colonies is carried out. And, later, the confirmation is carried out. This is done by incubation of the colony in brain-heart medium and rabbit plasma, in which it is determined positive if a large compact clot is observed [1]. Moreover, during my Master's Thesis I have been involved in the analisys of many different food samples as well as water for the detection of different microorganisms like Enterobacer, Salmonella, etc.